1993
DOI: 10.1111/j.1365-2958.1993.tb01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion within the metallothionein locus of cadmium‐tolerant Synechococcus PCC 6301 involving a highly iterated palindrome (HIP1)

Abstract: Genomic rearrangements involving amplification of metallothionein (MT) genes have been reported in metal-tolerant eukaryotes. Similarly, we have recently observed amplification and rearrangement of a prokaryotic MT locus, smt, in cells of Synechococcus PCC 6301 selected for Cd tolerance. Following the characterization of this locus, the altered smt region has now been isolated from a Cd-tolerant cell line, C3.2, and its nucleotide sequence determined. This has identified a deletion within smtB, which encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 32 publications
1
47
0
1
Order By: Relevance
“…A modified STRR primer viz., STRR mod based on the consensus sequence was synthesized by Zheng et al (2002) who reported the utility of this primer in differentiating symbiotic cyanobacteria from cycad roots. Another repetitive eight base sequence (5'GC-GATCGC3'), referred to as the Highly Iterated Palindrome (HIP1), which is uniquely and largely overrepresented in cyanobacterial genome, was first identified at the borders of a gene deletion in a cadmiumtolerant strain of Synecococcus PCC 6301 (Gupta et al 1993). While there are no comparable sequences to HIP1 in other organisms, the reasons for the overrepresentation of HIP1 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A modified STRR primer viz., STRR mod based on the consensus sequence was synthesized by Zheng et al (2002) who reported the utility of this primer in differentiating symbiotic cyanobacteria from cycad roots. Another repetitive eight base sequence (5'GC-GATCGC3'), referred to as the Highly Iterated Palindrome (HIP1), which is uniquely and largely overrepresented in cyanobacterial genome, was first identified at the borders of a gene deletion in a cadmiumtolerant strain of Synecococcus PCC 6301 (Gupta et al 1993). While there are no comparable sequences to HIP1 in other organisms, the reasons for the overrepresentation of HIP1 is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting finding is that the longest HIP1 gap (coordinates 43193-274, ~3.5 kb) corresponds to the putative replication origin. It has been suggested that HIP1 sites participate in homologous recombination and other sequence rearrangement events in cyanobacterial genomes (Gupta et al, 1993;Robinson et al, 1997). The absence of HIP1 sites in this region supports its importance in maintenance of pANL.…”
Section: Repetitive Sequencesmentioning
confidence: 85%
“…An octameric highly iterated palindrome (HIP1), GCGATCGC, is over-represented in DNA sequences of many cyanobacterial strains, including Synechococcus species (Gupta et al, 1993). The chromosome of S. elongatus PCC 7942 has 7,402 HIP1 sites, around 1 site per 364 bp.…”
Section: Repetitive Sequencesmentioning
confidence: 99%
“…The highly iterated palindromes, commonly referred to as HIP1, are a repetitive eight-base sequence (5′GCGATCGC 3′) which have been known to be exclusively over-represented in the cyanobacterial genome and more importantly have been regarded to have immense evolutionary footprints because of them being recombinational hotspots (Smith et al 1998;Selvakumar and Gopalaswamy 2008). The existence of these repetitive sequences was for the first time reported in calcium tolerant strain Synechococcus PCC 6301 (Gupta et al 1993). Thereafter, repetitive sequences have been widely considered as one of the most accepted tools for assessing the (Lee et al 1996;Garcia-Pichel et al 2001;Gugger et al 2002;Roeselers et al 2007;Valério et al 2009).…”
Section: Introductionmentioning
confidence: 99%